CHAOS UND FORM, RAUM UND ETHOS IN STIFTERS BUNTE STEINE. (October 2015) - Nitschke, Claudia; Cooper, Ian; Holmes, Deborah
ABSTRACT Form, order, and the desire to create structure are ubiquitous in Adalbert Stifter's work, both as theme and in the presentation of his oeuvre. It is striking that quotidian rituals and emergency situations such as thunder and snowstorms are often intrinsically tied to places. In Stifter's narratives the spatial concurrence of danger as a manifestation of formlessness, and structure as a potential remedy for the precarious situations, reveals a specific technique of stabilisation. This omnipresent need for stabilising rituals (occurring in a specific place) indirectly demonstrates that notions of transgression are integral to Stifter's texts, even though he consistently attempts to transform it into a certain structure: in this regard an individual and collective moral style of life is presented as the best and most natural way of coping with external forces by dint of an autonomous (but naturally pre‐ordained) order. Form, Ordnung und Streben nach Struktur sind bei Adalbert Stifter omnipräsent, sowohl als Thema in den Erzählungen wie auch als mise‐en‐abyme bei der textlichen Präsentation. Besonders auffällig ist dabei, dass für Stifter typische Ritualisierungen des Alltags sowie affektgeladene Ausnahmesituationen (etwa Gewitter oder Schneesturm) und ihre potentielle Regulierung intrinsisch an Örtlichkeiten geknüpft werden. Das spatiale Zusammenfallen von Gefahr als Strukturlosigkeit und Struktur als potentieller Rettung legt eine spezifische Stabilisierungstechnik offen, die hier in der räumlichen Verdichtung deutlich macht, wie stark Stifter Vorstellungen von Transgression in seine Texte integriert, auch wenn diese konsequent in einer 'Form' stabilisiert wird. Als strukturgebend erweist sich hier ein individueller oder kollektiver moralischer Lebensentwurf, der den externen Gewalten die eigene Ordnung entgegensetzt.